A Latent Profile Analysis of Work Engagement, Workaholism and Psychological Detachment: Differences in Well-being after work among Korean employees - Kang, SunA; Choi, BoYoung (Korean Journal of Industrial and Organizational Psychology, 2022)
This study identified the latent profile of two types of heavy work investment, namely workaholism and work engagement, by adding psychological detachment from work. Additionally, it was examined whether there were differences in well-being after work by each profile type. For this purpose, Latent Profile Analysis(LPA) was conducted using data of 548 korean employees in various occupations, and three types(workaholic, heavy work investors, disenaged) were confirmed as a result. There was a significant difference in all the well-being variables by type. The heavy work investors type showed the best well-being among the three types with the lowest emotional exhaustion, the highest positive affect, the middle level negative affect and the sleep quality. Our findings indicate that psychological detachment is an important factor that alleviates the detrimental effects of heavy work investment on employees’well-being and that work engagement can play a protecting role for employees’well-being even in absence of significant levels of psychological detachment.